2008
DOI: 10.12693/aphyspola.113.731
|View full text |Cite
|
Sign up to set email alerts
|

Stokes Shift and Band Gap Bowing in InxGa1-xN (0.060 ≤ x ≤ 0.105) Grown by Metalorganic Vapour Phase Epitaxy

Abstract: We presented the results of electrical and optical studies of the properties of In x Ga 1−x N epitaxial layers (0.060 ≤ x ≤ 0.105) grown by metalorganic vapour phase epitaxy. Resistivity and Hall effect measurements of the samples were carried out at room temperature. Optical properties of the samples were characterized by photoluminescence and optical absorption spectroscopy. The comparison between the photoluminescence and the optical absorption measurements gives the Stokes shift. We explained the observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Whereas, the shift in emission peaks from 580 nm to 583 nm and 630 nm to 632 nm was observed for the excitation wavelengths of 400 nm and 450 nm, respectively, when the substrate temperature increased from RT to 450 1C. This may be due to the variation in the optical bandgap (narrowing) of the material [36].…”
Section: Photoluminescence Propertiesmentioning
confidence: 92%
“…Whereas, the shift in emission peaks from 580 nm to 583 nm and 630 nm to 632 nm was observed for the excitation wavelengths of 400 nm and 450 nm, respectively, when the substrate temperature increased from RT to 450 1C. This may be due to the variation in the optical bandgap (narrowing) of the material [36].…”
Section: Photoluminescence Propertiesmentioning
confidence: 92%
“…To the best of the authors' knowledge there is no report available in the literature on the inelastic scattering time of InGaN. In a previous work [4], we showed that InGaN layers have a high bowing parameter ~3.6 eV, which indicates presence of disorder and defects in the structure of InGaN. These defects can induce localized levels in an impurity band.…”
Section: Introductionmentioning
confidence: 74%
“…Since the formation an impurity band in InGaN can be expected due to defects in its structure [4], we can consider the contribution of the Lorentz force to the MC. Then the MC at a given temperature, including both the WL effect and two-band model can be given by the expression [8,14], (where p is an index depending on scattering mechanism nature).…”
Section: Resultsmentioning
confidence: 99%
“…The electroplex emitting peak is red-shifted relative to the emissions of PVK and Bphen. In addition, the electroplex emission shifted to lower energy side due to the Stokes shift effect in respect of the HOMO(PVK)-LUMO(Bphen) difference for this transition [21]. As the applied voltage increases some electrons will be injected into the LUMO of PVK under the stronger electric field strength and could recombine with the holes at the HOMO level of PVK, leading to the enhancement of blue emission intensity and the decrease of ratio of red emission intensity to blue emission intensity.…”
Section: Resultsmentioning
confidence: 99%